ChemInform Abstract: Palladium‐Catalyzed Aminocarbonylation of Aryl Iodides Using Aqueous Ammonia. Issue 4 (28th January 2014) - Xu, Tongyu; Alper, Howard
Abstract Aminocarbonylation of aromatic iodides using aqueous ammonia in toluene is processed using Pd(OAc)2/CYTOP®292 (TPA) as catalyst.